2010
DOI: 10.1177/1933719110364550
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A and Serum Withdrawal Induced Changes in the Transcript Profile in Human Endometrial Endothelial Cells

Abstract: The changes in transcript profile induced by vascular endothelial growth factor (VEGF-A) and serum withdrawal in primary human endometrial endothelial cells (ECs) were investigated using microarrays, gene ontology and pathway analysis. Vascular endothelial growth factor A altered the levels of transcripts involved in angiogenesis, cell survival, and apoptosis, including up-and downregulation of AKT1, BAD, MIF, and IGFBP3 and ANGPT2, respectively. Serum deprivation induced downregulation of cell-cycle-related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Endometrial biopsy samples from four women at fertile age undergoing hysterectomy for benign medical conditions at Uppsala University Hospital were obtained, and cultures of endothelial and stromal cells were established, maintained, and characterized as previously described. 28,29 Several of our previous studies have demonstrated that there are no differences between HEECs from the proliferative and secretory menstrual phases concerning HEEC viability and proliferation as well as gene expression when exposed to VEGF-A, several different hormones and endocrine disrupting chemicals 29,30 -32 and therefore no comparison was made between cells from the two menstrual phases.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Endometrial biopsy samples from four women at fertile age undergoing hysterectomy for benign medical conditions at Uppsala University Hospital were obtained, and cultures of endothelial and stromal cells were established, maintained, and characterized as previously described. 28,29 Several of our previous studies have demonstrated that there are no differences between HEECs from the proliferative and secretory menstrual phases concerning HEEC viability and proliferation as well as gene expression when exposed to VEGF-A, several different hormones and endocrine disrupting chemicals 29,30 -32 and therefore no comparison was made between cells from the two menstrual phases.…”
Section: Cell Culturesmentioning
confidence: 99%
“…The method of isolation is a standard procedure at our lab and we have previously characterized the isolated HEE cells [Moberg et al 2010]. Premenopausal women with regular menstrual cycles, who underwent hysterectomy for benign medical conditions at Uppsala University Hospital, Sweden, were included.…”
Section: Hrg Peptidesmentioning
confidence: 99%
“…Moreover, basal ERK1/2 phosphorylation is reduced in the early phase of serum starvation, which is likely accountable for the observation that VEGF-A fails to further elevate ERK1/2 phosphorylation. Additionally, endothelial serum starvation alters the expression profile of a subset of genes controlling ERK1/2 activity and cell cycle progression [66]. In the late phase, the sensitivity of endothelial cells to VEGF-A is markedly reduced, as the VEGFR2:sFlt-1 ratio is dramatically lowered.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, serum starvation induces a cellular stress response linked to upregulation of VEGF-A mRNA levels [37]. Remarkably, out of 89 genes altered during endothelial cell stimulation with VEGF-A, 88 are also regulated during partial serum deprivation, demonstrating considerable linkage between cellular responses to these stimuli [38]. VEGFR2 is also a key mediator of endothelial cell survival during serum deprivation [39].…”
Section: Introductionmentioning
confidence: 98%